From the net to the Net : Atlantic Canada and the global economy - Sacouman, R. James, 1948-; Veltmeyer, Henry (Garamond Press, 2005)
"Globalization appears inevitable and inescapable in its effects, all countries and people having to adjust to an irresistible force the best way they can - to insert themselves into the process under the most favourable conditions, or to make the best deal possible with a single global economy based on capitalist principles." "From the Net to the Net looks at the dynamics of this process as well as strategic responses. Appearances to the contrary, the process of globalization in this regional context is by no means inevitable, nor is it immutable. Diverse organizations of people in an increasingly organized 'civil society' are coming together to mobilize the forces of opposition to globalization in its neoliberal form."--Jacket